Perbedaan Pembiayaan Model Bagi Hasil dan Non Bagi Hasil Terhadap Profitabilitas dan Resiko (Studi Kasus BMT Amanah Ummah) - Ilham Nur Agustha; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research is conducted to identify the relationship between profit sharing financing, non-profit-sharing, risk, and profitability of the BaitulMaalwatanwil. While the purpose of this study was conducted to determine the difference between the two financing available in BMT Amanah Ummah Karah Surabaya branch (profit sharing and non-sharing).The method used in this study is qualitative approach, using the case study method. The collection of the data done by linking the questions asked, the data collected with the conclusions drawn from interviews with secretaries and marketing lending at headquarter of BMT Amanah Ummah Karah Surabaya branch.The results showed that non-profit-sharing financing have a higher level of profitability than the profit sharing financing. Meanwhile, from the level of risk, profit sharing financing have a higher degree of risk compare to non-profit sharing financing. REFERENCESAl-Qur‟an dan Terjemahannya. 1971. Jakarta: Yayasan Penyelenggara Penerjemah/Penafsir Al-Qur‟an.Hamza, Ufika. 2008. Analisis Profitabilitas Baitul Maal Wa Tanwil Periode 2003-2007 (Studi pada BMY-MMU Pasuruan Cabang Wonorejo). Malang: Skripsi Program Sarjana UINKarim, Adiwarman A. 2006. Bank Islam: Analisis Fiqh dan Keuangan. Jakarta: PT Raja Grafindo.------------. 2008. Sejarah Pemikiran Ekonomi Islam. Jakarta: PT. Raja Grafindo Persada.Kasmir. 2007. Bank dan Lembaga Keuangan Lainnya. cet VI. Jakarta: PT Raja grafindo Persada, hlm 115-----------. 2007. Bank dan Lembaga Keuangan Lainnya. cet VI. Jakarta: PT Raja Grafindo Persada, 116 Majelis Ulama Indonesia. 2000. Kumpulan Fatwa Dewan Syariah Nasional. Jakarta: Republik IndonesiaRyandono, Muhammad Nafik Hadi. 2009. Bursa Efek dan Investasi Syariah. Jakarta: PT. Serambi Ilmu Semesta.---------------. 2008. Modul Disajikan Dalam Pelatihan Lembaga Keuangan Syariah. Inggris Islamic Finance Development Institute (IFDI)Yin, Robert K. 2006. Studi Kasus: Desain dan Metode. Jakarta: PT. Raja Grafindo Persada.